2017
DOI: 10.1016/j.applthermaleng.2017.05.163
|View full text |Cite
|
Sign up to set email alerts
|

Integrated energy simulation of a deep level mine cooling system through a combination of forward and first-principle models applied to system-side parameters

Abstract: Highlights• Proposition of an integrated mine cooling system energy modelling method.• The model is be calibrated with system measured or manufacturer data.• Major energy consuming devices include chillers, cooling towers, pumps and fans.• Model parameter identification achieved RMSRE values between 0.0114 and 0.0651.• An overall absolute average error between 2.5% and 3.5% was obtained. 2 AbstractMine cooling systems typically account for around 25% of the total electrical energy consumption of deep level min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 32 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…South African deep-level mines experience virgin rock temperatures of up to 60 °C [4] at increased mining depths, and are up to 4 km in depth [5]. Mines use cooling systems to maintain underground temperatures under the required threshold, but they use around 25% of a mine's total electricity consumption [6], [7]. With the rise in electrical costs, mines are forced to implement energy-saving initiatives to remain profitable.…”
Section: Energy Constraints In Deep-level Miningmentioning
confidence: 99%
See 1 more Smart Citation
“…South African deep-level mines experience virgin rock temperatures of up to 60 °C [4] at increased mining depths, and are up to 4 km in depth [5]. Mines use cooling systems to maintain underground temperatures under the required threshold, but they use around 25% of a mine's total electricity consumption [6], [7]. With the rise in electrical costs, mines are forced to implement energy-saving initiatives to remain profitable.…”
Section: Energy Constraints In Deep-level Miningmentioning
confidence: 99%
“…Dynamic simulations can provide a holistic view of a mine's cooling energy usage and the overall system service delivery. It can assist with outlining the impacts of changing one or a combination of subcomponents on the system [15]. To make well-informed decisions about reducing the system's total energy consumption and improving overall service delivery, an integrated investigation is required to evaluate the impact on the overall cooling system.…”
Section: Current Simulations and Cooling Strategiesmentioning
confidence: 99%
“…The thermal-hydraulic characteristics of the mine cooling system were studied by evaluating the energy consumption of the system with a simulation model in a holistic view. The results showed that creating a comfortable and healthy environment is possible without a significant increase in capital costs [10].…”
Section: Introductionmentioning
confidence: 99%
“…Since artificial refrigeration systems usually require the establishment of large refrigeration base stations, their construction and operating costs are relatively high. Many scholars have focused on reducing operation costs, implementing energy-saving technologies, and optimizing refrigeration systems [20][21][22][23]. In general, the artificial refrigeration method has a remarkable refrigeration effect, but is expensive, which limits its wide application in mines.…”
Section: Introductionmentioning
confidence: 99%